1994
DOI: 10.2118/22650-pa
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Huff 'n' Puff Revives Shallow Light-Oil-Depleted Reservoirs

Abstract: Cyclic CO 2 huff 'n' puff process in diverse reservoir conditions, such as immiscible, near-miscible, and miscible, has been tested in the laboratory and applied in the fields as a viable secondary or tertiary means to recover the residual oil in water flooded reservoirs or pressure depleted reservoirs. Recently, petroleum operators have shown increasingly interest in taking CO 2 huff 'n' puff process as a preferred option to extract light oil in low-pressure and low-permeability reservoirs.In this paper, expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Huff and puff processes have been studied in the field and laboratory as well as by reservoir simulation by many investigators (Bardon et al, 1991;Haskin and Alston, 1989;Palmer et al, 1986;Simpson, 1988). Torabi and Asghari (2004) performed a CO 2 huff and puff process in fractured porous media and high recovery rate of 48-94% were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Huff and puff processes have been studied in the field and laboratory as well as by reservoir simulation by many investigators (Bardon et al, 1991;Haskin and Alston, 1989;Palmer et al, 1986;Simpson, 1988). Torabi and Asghari (2004) performed a CO 2 huff and puff process in fractured porous media and high recovery rate of 48-94% were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, they found that soaking mainly affects the peak production rate after injection. Later, cyclic injection of carbon dioxide was utilized for heavy oil in California (Sankur and Emanuel 1983), Arkansas (Khatib et al 1981), and Turkey (Bardon et al 1986), and for light and medium types of oil in Kentucky (Bardon et al 1994), Texas (Haskin and Alston 1989), and Louisiana (Monger and Coma 1988). In the 1990s and 2000s, nitrogen and mixtures with nitrogen were proposed and successfully applied (Shayegi et al 1996;Miller and Gaudin 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The EOR by CO2 foaming with using huff-and-puff process has been applied either light oil [1,2] or heavy oil [3,4]. The procedure of huff-and-puff method is the repeating of injection and production which is called pressurization and depressurization or carbonation and liberation [4].…”
Section: Introductionmentioning
confidence: 99%